2014
DOI: 10.1002/ams2.87
|View full text |Cite
|
Sign up to set email alerts
|

Delayed visceral ischemia induced by type B aortic dissection

Abstract: Case: A 56-year-old man presented with a sudden severe abdominal pain 13 days after the onset of type B acute aortic dissection.Chest computed tomography revealed type B aortic dissection, and the true lumen was narrowed by the expanding false lumen. Blood flow through the celiac trunk, superior mesenteric artery, and left renal artery was reduced. Blood flow through the distal abdominal aorta and bilateral femoral arteries was clearly recognized. Laboratory findings such as transaminases were rapidly worsenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…Reports [ 1 , 3 ] based on the data from the International Registry of Acute Aortic Dissection showed that 71 cases (7.6%) were complicated with mesenteric ischemia, and 26 cases died (36.6%) out of 1034 cases of type B aortic dissection from 1996 to 2013. Although there was no clear distinction between occlusive and nonocclusive patients in this paper, it was confirmed by other case reports that aortic dissection could cause NOMI [ 10 ].…”
Section: Discussionsupporting
confidence: 65%
“…Reports [ 1 , 3 ] based on the data from the International Registry of Acute Aortic Dissection showed that 71 cases (7.6%) were complicated with mesenteric ischemia, and 26 cases died (36.6%) out of 1034 cases of type B aortic dissection from 1996 to 2013. Although there was no clear distinction between occlusive and nonocclusive patients in this paper, it was confirmed by other case reports that aortic dissection could cause NOMI [ 10 ].…”
Section: Discussionsupporting
confidence: 65%
“…No current guidelines for endovascular aortic repair specially mention the risk for IMA obstruction. To our knowledge, this is the first case report of sole IMA obstruction–induced mesenteric ischemia as a complication of type B AD ( Table 1 ) ( 4 , 5 , 6 , 7 , 8 ).…”
Section: Discussionmentioning
confidence: 81%
“…(2016) ( 5 ) #3 56 M Acute type B 13 days after the onset Dynamic CA and SMA obstruction Not performed Resection of the intimal flap Kurumisawa et al. (2015) ( 6 ) #4 55 F Acute type B 5 weeks after the onset Static SMA obstruction Stenosis of the SMA Stent placement in the SMA Sasaki et al. (2019) ( 7 ) #5 41 M Acute type B At admission Dynamic SMA obstruction Stenosis of the SMA TEVAR Tshomba et al.…”
Section: Discussionmentioning
confidence: 99%